Association of SCN1A Gene Polymorphism with Phenytoin Response in Patients with Epilepsy: Relevance of Stratification by the History of Febrile Seizure - Khairani, Atitya Fithri; Sutarni, Sri; Sholikhah, Eti Nurwening; Malueka, Rusdy Ghazali; Luthffia, Audiza; Vidyanti, Amelia Nur (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The SCN1A gene encodes the NaV1.1 sodium channel in the central nervous system that serves as the target for phenytoin. Our study aimed to investigate the association of SCN1A polymorphism (SNP rs3812718) with phenytoin response. MATERIALS AND METHODS: A total of 120 epileptic patients who had received phenytoin for at least 1 year were enrolled in the study and genotyped using the TaqMan assay. They were classified into phenytoin-responsive (n = 62) and phenytoin unresponsive groups (n = 58). Patients were also stratified according to the history of febrile seizure (24 in the febrile seizure subgroup; 96 patients in the no history of febrile seizure subgroup) and epilepsy etiology (47 in idiopathic; 73 in the symptomatic + cryptogenic subgroup). RESULTS: The frequency of AA (19% vs. 11.3%) and AG genotypes (43.1% vs. 40.3%) was found to be more frequent in phenytoin unresponsive. GG genotypes dominated in the phenytoin responsive group (37.9% vs. 48.4%) but were not statistically significant (p > 0.05). We identified two variables associated with phenytoin response: the etiology of epilepsy (p = 0.012) and history of febrile seizure (0.014). A significant positive association between the rs3812718 genotype and phenytoin response was found when patients were stratified by a history of febrile seizures. In patients without a history of febrile seizures, the AA genotype had a higher risk of phenytoin unresponsiveness than the GG genotype (p = 0.048; OR 3.73, 95% CI: 1.01–13.78). CONCLUSION: There was no significant association between the rs3812718 polymorphism and phenytoin responsiveness in patients with epilepsy. In the patients without a history of febrile seizure subgroup, AA increased the risk of phenytoin unresponsiveness compared to the GG genotype.